AVALIAÇÃO DE PARÂMETROS BIOQUÍMICOS E HEMATOLÓGICOS DE PACIENTES COM DOENÇA DE ALZHEIMER DE GUARAPUAVA-PR - Paganini, Juliane Cristina de Almeida (2014)
Among of the dementias that affect the old age population Alzheimer`s disease is the most prevalent, it is a neurodegenerative, progressive and irreversible pathology. The diagnosis is made by exclusion of other dementias, applying standardized questionnaires and exams of neuroimaging. However, there is no exact diagnosis for these disease yet and the definitive diagnosis is done after the patient`s death, using brain histological analysis. This present study has for objective avaliat biochemical, hematological, demographic, socioeconomic and cognitive data in different stages of AD in patients with Alzheimer`s who users Specializing Component of Pharmaceutical Care at public health in Guarapuava-Paraná. The sample comprised 30 patients, of whom a blood sample was collected for analysis. The aim of this study was to establish a relationship of frequency and occurrence of biochemical and hematological parameters and the onset of disease. Another approach is to trace socioeconomic and demographic profile of patients affected by AD. Our results do not allow to find clinically significant differences between all analyzed parameters and the occurrence of the disease.